SYNCHRONOUS BALANCED OPERATION OF OPEN-END WINDING MOTOR DRIVE WITH TWO ISOLATED DC-SOURCES - Oleschuk V.; Griva G.; Prudeak R.; Sizov A. (Problems of the Regional Energetics)
Novel method of synchronized pulsewidth modulation (PWM) has been applied for balanced control of dual inverter-fed drive with an open-end-winding induction motor, supplied by two isolated dc-sources. Simulations give the behavior of dual inverter-fed systems with continuous and discontinuous versions of synchronized PWM.